2009
DOI: 10.1080/02640410903207416
|View full text |Cite
|
Sign up to set email alerts
|

Activity profiles and physical demands of elite women's water polo match play

Abstract: The aim of this study was to quantify the movement patterns of contemporary elite women's water polo match play. Thirty-three player matches (centre, n = 15 and perimeter, n = 18) were analysed using video-based time-motion analysis. Frequency and duration of individual movements and distance swum were assessed. Mean match time and playing time were 69:48 +/- 04.30 min:s and 33:14 +/- 14:40 min:s, respectively. Players performed 330 +/- 158 discrete movements per match, representing a change in movement every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 12 publications
0
48
0
1
Order By: Relevance
“…These activities may progressively increase the metabolic perturbation and cardiovascular strain leading to both upperbody and lower-body performance deterioration. Previous studies have reported reduced mean heart rate toward the last minutes of a water polo game (5,18,21) and a substantial reduction of the number of high-intensity activities in the fourth period of the game compared with the first one (16,26).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These activities may progressively increase the metabolic perturbation and cardiovascular strain leading to both upperbody and lower-body performance deterioration. Previous studies have reported reduced mean heart rate toward the last minutes of a water polo game (5,18,21) and a substantial reduction of the number of high-intensity activities in the fourth period of the game compared with the first one (16,26).…”
Section: Introductionmentioning
confidence: 98%
“…Repeated sprints together with several explosive-type activities and dynamic body contacts among opponents (high-intensity activities), interspersed with low-intensity efforts (slow swimming and treading water), frequently occur during a water polo game (19,26). These activities may progressively increase the metabolic perturbation and cardiovascular strain leading to both upperbody and lower-body performance deterioration.…”
Section: Introductionmentioning
confidence: 98%
“…W ater polo is a very stressful body-contact team sport that combines high-intensity short duration efforts such as swimming at maximum speed, elevation of the body from the water, and throwing, with rest or low intensity actions (31). In addition, players need considerable strength to hit, block, push, and hold other players during game play (28,33).…”
Section: Introductionmentioning
confidence: 99%
“…Water polo is a popular team sport that requires a welldeveloped level of swimming fitness; strength and power to compete successfully in contact situations; technical skills in catching, passing, and shooting the ball; and decision-making and team strategies and tactics (Tan et al, 2009). The energetic demands of water polo can be characterized as highly intermittent, ranging from relatively low-intensity activity such as treading water to sudden bursts of supramaximal power during competition and practice (Pinnington et al, 1988;Smith, 1998).…”
mentioning
confidence: 99%